2010
DOI: 10.1111/j.1365-3032.2010.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Hygropreference behaviour and humidity detection in the yellow-spined bamboo locust, Ceracris kiangsu

Abstract: Water is a critical resource for all terrestrial insects. The yellow-spined bamboo locust Ceracris kiangsu Tsai (Oedipodidae: Orthoptera), matures, copulates and reproduces in the summer and adults are observed mud-puddling in human urine-contaminated materials on hot days. Besides obtaining NaCl and NH 4 HCO 3 , the locust may also compensate for water deficiency. In a dual-choice test in the laboratory, adults prefer to remain on wet rather than dry filter paper at high temperature (36 • C). The females are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…They are capable of interchanging humidity with environment trough the spiracles and during the ßight, some spiracles are continuously open (Gullan and Cranston 2000) increasing water loss (Yu et al 2010). This water loss could be controlled by a reduction in locomotion (Prates et al 2005) or moving to areas according to water vapor content in the air (Martṍnez and Hardie 2009).…”
Section: Discussionmentioning
confidence: 98%
“…They are capable of interchanging humidity with environment trough the spiracles and during the ßight, some spiracles are continuously open (Gullan and Cranston 2000) increasing water loss (Yu et al 2010). This water loss could be controlled by a reduction in locomotion (Prates et al 2005) or moving to areas according to water vapor content in the air (Martṍnez and Hardie 2009).…”
Section: Discussionmentioning
confidence: 98%
“…This decrease in density is in agreement with the mechanisms of water regulation. High levels of humidity and gregariousness contribute to reducing water loss 11,14,16,17 . In fact, a classical geometric hypothesis is put forth to explain the individual reduction of water loss in an aggregate.…”
Section: Discussionmentioning
confidence: 99%
“…To do so, most arthropods benefit from different mechanisms to counterbalance water loss 8 . These mechanisms can be physiological, by modifying the water content of their faeces 9 or their respiration rate 10 , They can also be behavioural, such as hygrotaxis to acquire environmental moisture 11 through fog basking 12 or forming an aggregate to reduce individual water loss 1316 mainly by reducing the individual surface area exposed to the air 17 .…”
Section: Introductionmentioning
confidence: 99%
“…As with most insects, olfaction plays a key role in many functional aspects of C. kiangsu , including mate recognition, oviposition site location, foraging, and avoidance of predators and other dangers ( Schiestl, 2010 ; Leal, 2013 ; Wyatt, 2014 ). Previous studies of C. kiangsu , however, have focused mainly on behavior ( Yu et al, 2010 ), ecology ( Zhang and Zuo, 2005 ), and phylogeographics ( Fan et al, 2014 ). Shen et al (2009) first reported the mud-puddling behavior of C. kiangsu : their results showed that salt (NaCl) and nitrogen (NH 4 HCO 3 and NH 4 Cl) in human urine can stimulate the directional movement of C. kiangsu .…”
Section: Introductionmentioning
confidence: 99%